EXPLORING COOPERATIVE LEARNING METHOD AS THE STRATEGY TO IMPROVE STUDENTS' WRITING SKILL: A Quasi-Experimental Study of Teaching Writing at One Senior High School in Bandung - Agrian, Anne Denti (2015)
Penelitian ini bertujuan untuk menggali efektivitas metode pembelajaran kooperatif untuk meningkatkan kemampuan menulis siswa serta menjelaskan respon mereka terhadap penggunaan metode ini. Sebuah desain penelitian kuasi-eksperimental diterapkan dengan tiga instrumen untuk mengumpulkan data, yaitu pretest, posttest dan kuesioner. Responden yang terlibat adalah 58 siswa kelas XI dan data yang terkempul dihitung dengan menggunakan IBM SPSS v.20. Hasil temuan menunjukkan bahwa metode pembelajaran kooperatif telah berhasil meningkatkan kemampuan menulis siswa. Selanjutnya, perhitungan ukuran efek menunjukkan efek besar dari metode ini dalam meningkatkan nilai menulis siswa. Sebenarnya, pelaksanaan pembelajaran kooperatif, yang bukan merupakan kerja kelompok biasa, harus mengikuti beberapa persyaratan sehingga tercipta interaksi kelas yang lebih efektif. ---------- This research paper is aimed at exploring the effectiveness of cooperative learning method to improve students' writing skill as well as describing their responses to the use of this method. A quasi-experimental research design was employed with three instruments to collect data, namely pretest, posttest and questionnaire. The respondents were 58 eleventh grade students and the data gathered were computed using SPSS (Statistical Package for the Social Sciences) version 20. The results reveal that the cooperative learning method has successfully improved students' writing skill. Further, the calculation of effect size indicates the large effect of this method in improving students' writing score. In fact, the implementation of cooperative learning, which is not a common group work, has to follow several requirements so as to create more effective classroom interactions.